TUKANG KABA IN NOVEL JEMPUT TERBAWA BY PINTO ANUGRAH: TUKANG KABA DALAM NOVEL JEMPUT TERBAWA KARYA PINTO ANUGRAH - Eka Meigalia; Yerri Satria Putra (LLDIKTI Wilayah X, 2021)
This study aims to explain the functions and roles of the kaba artisans in Minangkabau society and culture and the parts and functions of the kaba artisans themselves in Pinto Anugrah's novel Jemput Terbawa. The research method used is qualitative with data collection techniques in the form of reading and recording. The data were analyzed and interpreted with a literary, anthropological approach. The results of the research are an introduction and closing of the story. It regulates the course of the story, saving the lives of several characters in the story, protecting the author from his own story that might be considered incorrect, and reinforcing his role in presenting stories that have been up to now. It develops in society. Through this novel, the author has presented the role and function of the kaba craftsman and his role and function as a storyteller in the past in the Minangkabau community. The craftsman of the kaba is considered to influence the reader of the work and the craftsman of the kaba to influence his listeners.